الاصلاح الاجتماعي عند جمعية العلماء المسلمين الجزائرين - شرقي, أيوب; دهاش, الصادق (جامعة الوادي - University of Eloued, 2022)
كان لجمعية العلماء المسلمين الجزائريين دورا فعالا في الإصلاح الاجتماعي لدى المجتمعات خاصة المجتمع الجزائري في ظل الاستعمار الفرنسي الذي أدى إلى الانحطاط الاجتماعي، لذا ساهمت الجمعية في تطور المرأة وتعليمها، وكذا تنشئة الشباب وإرشادهم إلى الطريق الحق والاستعمار من خلال إنشاء المدارس والنوادي الثقافية، كما أن الجمعية لم تقتصر على الاهتمام بالمرأة والشباب فقط، بل تعدت اهتماماتها بالأطفال الصغار وإعطائهم حقوقهم من التعليم وحمايتهم من الآفات الاجتماعية. The Association of Algerian Muslim Scholars had an active role in social reform in societies, especially Algerian society, in light of French colonialism, which led to social degeneration. Therefore, the association contributed to the development and education of women, as well as educating young people and guiding them to the right path and colonialism through the establishment of schools and cultural clubs. The association was not limited to caring for women and young people only, but rather its concerns went beyond young children, giving them their rights to education and protecting them from social evils.
مقال
Keywords: جمعية العلماء المسلمين ; الاصلاح الاجتماعي ; المرأة ; الشباب; Muslimscholars association, social reform, women, young childen